Detection of human cytomegalovirus (HCMV) DNA in HCMV IgM and IgG positive samples / Issabella Febrie Amot - Febrie Amot, Issabella (2015)
Human cytomegalovirus (HCMV) is a causative agent for HCMV infection that serves as the main cause of morbidity and mortality in immunocompetent individuals such as immunosuppressed recipient in solid organ transplant (SOT), immunod eficiency patients in the case of HIV and AIDS, cancer patients and infants. In Malaysia, there are few studies that are conducted focusing on the detection of HCMV diagnosis marker such as HCMV DNA among population in tertiary hospitals. Thus, in this preliminary study, the objective is to detect the presence of HCMV DNA in HCMV IgM and IgG positive samples. A total of 66 HCMV positive samples that consists of 33 IgM and IgG serum respectively, are collected from the Virology Laboratory under the Department of Pathology in HUKL. These samples are extracted according to the provided protocol by the manufactures, in order to get the purified DNA for the real time polymerase reaction (qPCR) assay. Higher concentration of HCMV DNA is detected in HCMV IgM samples with high specificity of the amplification reaction. Whereas, the HCMV DNA detection is lower in IgG samples and the specificity of the amplification reaction is also less specific. The validity and specificity of qPCR assay for both sample groups are achieved. In conclusion, HCMV DNA is detectable in serum samples using qPCR detection assay with a higher percentage (100%) of HCMV DNA concentrations are detected in the HCMV IgM positive samples but a lower percentage (79%) is seen HCMV IgG positive samples.